Assessment of different turbulence models in simulating axisymmetric flow in suddenly expanded nozzles - Afghan Khan, Sher; Owais Ali, Mir; Mohammed Riyadh, Miah; Hossen, Zahid; Mahdi Arefin, Nafis (International Journal of Engineering and Technology, 2018)
A numerical simulation was carried out to compare various turbulence models simulating axisymmetric nozzle flow past suddenly expanded ducts. The simulations were done for L/D = 10. The convergent-divergent nozzle has been modeled and simulated using the turbulence models: The Standard k-Îµ model, The Standard k-Ï‰ model and The SST k-Ï‰ model. Numerical simulations were done for Mach numbers 1.87, 2.2, and 2.58 and the nozzles were operated for NPRs in the range from 3 to 11. From the numerical analysis it is apparent that for a given Mach number and effect of NPR will result in maximum gain or loss of pressure. Numerical results are in good agreement with the experimental results.Â Â